Pelatihan Penerapan Teknologi Mesin Retort Cerdas untuk Menambah Daya Simpan Produk Olahan Jamur Tiram bagi Anggota Kelompok UPPKA Rizky Lancar Kelurahan Pongangan Gunungpati Semarang: Training on the Application of Smart Retort Machine Technology to Increase the Shelf Life of Processed Oyster Mushroom Products for UPPKA Group Members Rizky Lancar, Pongangan Village, Gunungpati, Semarang - Sukur, Muji; Februariyanti, Herny; Sari, Anisa Rachma; Nurraharjo, Eddy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Food preservation is a crucial aspect of the food industry, especially to extend shelf life, maintain quality, and ensure consumption safety. Preservation methods such as pasteurization and sterilization effectively inhibit the growth of pathogenic microorganisms without reducing the nutritional value of food. The UPPKA